Impact of Climate Change Disclosure on Financial Performance: An Analysis of Indian Firms - Kumar, Praveen; Firoz, Mohammad (Journal of Environmental Accounting and Management, 2026)
This paper investigated the relationship between the climate change disclosure and the firms’ financial performance in the Indian context. The climate change disclosure scores assigned by the Carbon Disclosure Project (CDP) survey to 44 participating Indian firms during 2011 to 2015 is being used to determine the extent of climate change disclosure. Further, Return on Equity (ROE) and Return on Assets (ROA) are being used to proxy the sample firms’ financial performance. After controlling for industry-and firm-specific ariables, we observed that the ROE will be higher for companies having higher environmental disclosure scores comparatively the companies having low environmental disclosure scores. Moreover, the results of the regression analysis revealed that the market rerceives the voluntary climate change disclosure as a positive corporate initiative, leading to significant positive regression coefficient. However, this study did not find any evidence to supports that the climate change disclosure affects ROA. These findings are crucial for managers and the investors to assess the economic consequences of voluntary environmental disclosures by the firms operating in emerging economies.